The value of the human milk fat globule membrane antigen HMFG2 in epithelial ovarian cancer monitoring: comparison with CA125. - Fisken, J. (Nature Publishing Group, 1993)
We assayed serum HMFG2 in serial samples from 215 primary epithelial ovarian cancer patients using an 'in-house' single determinant ELISA, 45% of patients with stage I, 54% with stage II, 61% with stage III and 75% with stage IV disease had elevated serum HMFG2. Post-operative levels were significantly related with residual tumour volume (P < 0.005), and fell in the majority of responders, although the association with response to first-line chemotherapy was not significant. HMFG2 had a sensitivity of 50% specificity of 83%, accuracy of 61%, PVP of 86% and PVN of 45% for disease at second-look laparotomy. Serial levels gave a lead time to clinical relapse in 47% of patients who responded to therapy, including one patient with negative CA125 levels. HMFG, paralleled CA125 in many respects, although it was elevated in fewer patients. In a stepwise discriminant analysis, HMFG2 added to the discrimination of CA125 (r = 0.183, P < 0.005), although additional accurate information was only given in patients with advanced poorly differentiated serous cystadenocarcinoma. Given that HMFG2 is expressed in few patients who are CA125 negative it is unlikely that it will have a significant clinical impact upon patient management.